Disentangling the welfarism/extra-welfarism distinction: Towards a more fine-grained categorization - Ruben Andreas Sakowsky (Health Economics, 2021)
In health economics, the distinction between welfarism and extra-welfarism has been employed to discuss various epistemological and normative differences between health evaluation approaches. However, a clear consensus on the definition of either welfarism, extra-welfarism, or the differences between the two sets of approaches has not emerged. I propose an alternative set of distinctions that allows for a more fine-grained categorization of health evaluation approaches. This categorization focuses on five dimensions: (1) the maximand of an evaluation approach, (2) its sensitivity toward normative concerns that defy compensation, (3) its position on which groups of individuals or collective entities act as sources of values, (4) its sensitivity to changes of mind, and (5) the inclusion of process-external values.
Keywords: 330; deliberative democracy; ethics; philosophy of health economics; political philosophy